Aplikasi Dominating Set untuk Irigasi Sawah - Muhlisatul Mahmudah (FKIP Universitas Islam Jember, 2018)
One of the theories developed in graph theory is the dominating set. Dominating set is a concept of determining the minimum point on the graph with the provision of a point as dominating set to reach the point that is around it. The smallest cardinality of the dominating set is called the domination number denoted by (G). Given graph G with point V and E side, let D be a subset of V. If each point of VD is adjacent at least one point from D, then D is said dominating set in graph G. Currently a lot of applications from dominating set, one of which is making irrigation fields. Wetland irrigation is needed to irrigate the rice fields so that the rice field is not short of water and can irrigate sufficiently, but it takes as little as possible for irrigation making in order to irrigate the rice field well. The research focuses on application of dominating set to rice field irrigation. Keywords: dominating sets, rice field irrigation